الخدمات الحكومية المقدمة وعلاقتها في دمج أطفال اضطراب طيف التوحد في التعليم العام في المنطقة الشرقية وفق رؤية 2030 بالمملكة العربية السعودية - سلوى العسيري
This current study attempts to investigate the possible relationships between services offered to children with autism spectrum disorder on the one hand and their inclusion academically, behaviorally, skillfully and socially among public school students in the Northeast of the Kingdom of Saudi Arabia on the other hand. It also aimed to study the differences between components of services offered and types of inclusions across participant demographic variables. The study sample consisted of 732 teachers of Dammam Governorate in the Eastern Province, using a simple random sampling technique. This technique was used to give each participant equal opportunity and have an equal sample representative in the study. The researcher constructed the instrument based on the literature review due to the lack of a valid instrument that precisely measures what she intended to measure. Several statistical methods were used to analyze the collected data, such as Exploratory Factor Analysis (EFA), Multiple Linear Regression, and Multivariance Analysis of variance (MANOVA). The EFA was used to summarize the individual items into their latent variables and investigate the instrument's construct validity. Moreover, Multiple Linear Regression was utilized to study the potential relationships among the constructs of the study, while MANOVA was used to examine the relationship among services offered to autistic children and their integrations and inclusions across sample demographic variables. The results of EFA suggested that the services provided for autistic children and their inclusion instruments were loaded according to predetermined theory, indicating strong construct validity. Furthermore, the Multiple Linear Regression Analysis found a statistically positive significant relationship between services offered components on the one hand and their academic, behaviours, skill and social’s inclusions on the other hand, which indicated the higher level of effectiveness of services offered among the selected subjects, the higher the autistic children’s inclusion and integration would be. The analysis also showed statistically significant differences between the services provided components across gender, age, specialization, qualification, experience and types of schools. This means that the effectiveness of services offered and their ability for autistic children integration depends largely on the gender of services providers, their age, specialisation, qualification, experiences and types of schools, respectively.